Evaluation of vaccination status of health care workers for recommended vaccines and their acceptance of SARS-CoV-2 vaccines. Issue 5 (30th November 2022) - Oygar, Pembe Derin; Büyükçam, Ayşe; Sahbudak Bal, Zumrut; Dalgıç, Nazan; Bozdemir, Şefika Elmas; Karbuz, Adem; Çetin, Benhur Şirvan; Kara, Yalçın; Çetin, Ceren; Hatipoğlu, Nevin; Uygun, Hatice; Aygün, Fatma Deniz; et al.
ABSTRACT: Introduction: Health care workers (HCWs) are disproportionately exposed to infectious diseases and play a role in nosocomial transmission, making them a key demographic for vaccination. HCW vaccination rates are not optimal in many countries; hence, compulsory vaccination policies have been implemented in some countries. Although these policies are effective and necessary under certain conditions, resolving HCWs' hesitancies and misconceptions about vaccines is crucial. HCWs have the advantage of direct contact with patients; hence, they can respond to safety concerns, explain the benefits of vaccination, and counter antivaccine campaigns that escalate during pandemics, as has been observed with COVID-19. Method: A short survey was carried out in May–June 2020 on the vaccination status of HCWs working with pediatric patients with COVID-19. The survey inquired about their vaccination status (mumps/measles/rubella [MMR], varicella, influenza, and diphtheria/tetanus [dT]) and willingness to receive hypothetical future COVID-19 vaccines. The respondents were grouped according to gender, age, occupation, and region. Results: In total, 4927 HCWs responded to the survey. Most were young, healthy adults. The overall vaccination rates were 57.8% for dT in the past 10 years, 44.5% for MMR, 33.2% for varicella, and 13.5% for influenza. Vaccination rates were the highest among physicians. The majority of HCWs (81%) stated that they would be willing to receive COVID-19 vaccines. Conclusion: Although vaccination rates for well-established vaccines were low, a majority of HCWs were willing to receive COVID-19 vaccines when available. Education and administrative trust should be enhanced to increase vaccination rates among HCWs.